Studi komunitas Kepiting Biola (Uca sp.) Pada Ekosistem Mangrove di Kawasan Mangrove Curahsawo Probolinggo, Jawa Timur - Agung Riswandi; Endang Yuli H; Mulyanto Mulyanto (Faculty of Science and Technology University Ibrahimy, 2019)
Fiddler crab (Uca sp.)one of the crabs that inhabit the intertidal area, especially around the mangrove forest research was conducted in the mangrove areas Curahsawo, district of Gending, Probolinggo, East Java in April 2017. The aim of this study is to determine the structure community violin crabs in the mangrove areas Curahsawo Probolinggo. The measured parameters namely pH, soil organic matter and soil texture. Sampling point there are three stations, namely station 1 is mangrove area, station 2 is in the pond area, the station 3 is the estuary area. Results of measurement of environmental quality at the location of research is soil pH among 7.09 to 8.03, soil organic matter among 1.027% to 3.106%, and the type of soil is sandy clay and dusty clay. fiddler crabs are found in mangrove ecosystem Curahsawo there are 6 types of Uca rosea, Uca lactea, vocans Uca, Uca perplexa, dussumieri Uca, Uca demani. The highest density of crabs is Uca perplexa as much as 16 ind/m2, the lowest type of Uca demani 4 ind/m2. Value diversity fiddler crabs in mangrove ecosystem Sawo relatively standart is 1,56. The value of existing dominance is 0,96. Index violin crab distribution patterns in the Mangrove Ecosystem Munitions Sawo is uniform for Uca lactea, Uca vocans, Uca dussumieri , Uca demani and clumped to Uca rosea and Uca perplexa. The result of the spread of fiddler crab to the type of soil texture is very visible on the Uca perplexa since spread across all points of soil sampling with the number 6 ind/m2 to 16 ind/m2 in the texture of clay and sandy loam.